Dr. Paul Holden — Deep Plane Facelift — Scottsdale - Holden, Paul (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Paul Holden, practicing in Scottsdale, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003163; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; scottsdale